(untitled) (Szociológiai Szemle, 2024)
The paper presents the actors and the newly recreated sets of relations of the agrarian economy of an agricultural market town of the Plain. The actors are a large state factory, two co-operatives, one working in a traditional way and one in the form of a holding; medium size factories organised as limited companies; co-operations based on the commonality of ownership; enterprises of gardening, animal husbandry and plant production, having a mixed cultivation or offering mechanised services; finally a few thousand small producers, the new landowners - this agrarian society is an articulated one and rich in actors. Relationship among the actors is characterised by conflict and almost by fighting. Struggle has crossed over the professional boundaries of interest representation and has been going on in the arena of local politocs and not only for better market positions and/or for retaining the already acquired positions. Land, having a symbolic value besides the real one, is at stake, together with the legitimation of the possession and/or use of implements, which would be accompained by making the set of oriteria of local validity accapted. At the same time no group of the actors is able to force out the others from competition for a long time and thus prove that it has ’more right’ to the ownership of land and the other means of production than its rivals, and thus a larger respect would justly surround them in local public life. Apparently the position and strength of interest representetion of the different groups are balanced. At the same time this society - despite all conflict - is characterised by a kind of common tolerance based on experience, or, with some exaggeration on fate; here everybody knows what does it mean to ’trouble with and work along’ with land.